The Influence of Transformational Leadership Style and Internal Communication on Employee Engagement at Haivo Group, Surabaya - Valiza Eka Putri; Maharani Ikaningtyas (Universitas KH. Abdul Chalim Mojokerto, 2026)
The study was conducted to understand the influence of transformational leadership style and internal communication on the level of employee engagement at Haivo Group, Surabaya. The method applied was quantitative and questionnaires as data collection techniques. The population selected by the author included all employees who work and are active in the Haivo Group Surabaya City environment. The sample determination was carried out using a non-probability sampling technique with a saturated sampling method, namely all members of the population were made respondents to the study. The number of samples collected was 50 respondents. The data obtained were then analyzed using SPSS version 26 through multiple linear regression analysis. The results of the analysis showed that transformational leadership style and internal communication simultaneously have a significant influence on employee engagement. However, when broken down partially, only internal communication has a significant influence, while transformational leadership style does not have a significant influence when viewed separately. These findings indicate that employee engagement at Haivo Group, Surabaya is more influenced by the effectiveness of internal communication than by transformational leadership style. Therefore, to improve employee engagement, management is advised to prioritize improving the quality of internal communication that is more intense, open, and consistent, and optimize the implementation of an adaptive transformational leadership style.